2018
DOI: 10.1158/1535-7163.targ-17-b043
|View full text |Cite
|
Sign up to set email alerts
|

Abstract B043: Mithramycin-SA analogues with reduced toxicity for the treatment of ETS transcription factor-driven tumors

Abstract: Introduction Chromosomal translocations involving the ETS family of transcription factors are common in Ewing sarcoma, prostate cancer, and leukemia. These translocations lead in overexpression of aberrant ETS transcription factors, which drive tumorigenesis. Mithramycin (MTM) was shown to inhibit EWS/FLI1, the most common ETS related transcription factor in Ewing sarcoma, presumably through interference at its DNA binding sites on promoter regions. However, MTM has a short half‐life and a narrow therapeutic w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Using the free carboxylic acid group in the 3-side chain of MTMSA, we coupled natural amino acids and small molecules to generate a series of analogues, 10 out of which MTMSA-Trp ( 3 , Figure 1) and MTMSA-Phe ( 4 , Figure 1) were found to have cytotoxicity comparable to that of MTM ( 1 ). 11 Most importantly, we demonstrated with crystallography studies that the 3-side chain of the MTMSA analogues can interact with FLI1. 12 In such complexes, aromatic 3-side chain MTMSA derivatives have sufficient length to directly interact with the FLI1 DNA binding domain of EWS-FLI1, reflecting the in vitro potency of MTMSA-Trp ( 3 ) and MTMSA-Phe ( 4 ) against Ewing sarcoma.…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations
“…Using the free carboxylic acid group in the 3-side chain of MTMSA, we coupled natural amino acids and small molecules to generate a series of analogues, 10 out of which MTMSA-Trp ( 3 , Figure 1) and MTMSA-Phe ( 4 , Figure 1) were found to have cytotoxicity comparable to that of MTM ( 1 ). 11 Most importantly, we demonstrated with crystallography studies that the 3-side chain of the MTMSA analogues can interact with FLI1. 12 In such complexes, aromatic 3-side chain MTMSA derivatives have sufficient length to directly interact with the FLI1 DNA binding domain of EWS-FLI1, reflecting the in vitro potency of MTMSA-Trp ( 3 ) and MTMSA-Phe ( 4 ) against Ewing sarcoma.…”
Section: Introductionmentioning
confidence: 77%
“…Initial pharmacological studies showed that both MTMSA-Trp ( 3 ) and MTMSA-Phe ( 4 ) appeared to have the potential to overcome the limitation of MTM ( 1 ), with MTMSA-Trp ( 3 ) being the more cytotoxic of the two derivatives (Table 3, entry 10). 11 However, their selectivity toward Ewing sarcoma cell lines was only slightly improved compared to MTM ( 1 ) (Table 3). We chose MTMSA-Trp ( 3 ) as a starting point to better understand and improve its potential binding properties to EWS-FLI1 by varying its electronic, steric, and hydrogen bonding properties of the tryptophan residue, with the major objective to increase the selectivity of it toward Ewing sarcoma cell lines while maintaining a cytotoxic activity comparable to MTM ( 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations